2014
DOI: 10.3109/21691401.2014.922568
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiber: Synthesis and biomedical applications

Abstract: Electrospinning uses an electrical charge to draw very fine (typically on the micro or nano scale) fibers from a liquid. Electrospinning or electrostatic spinning shares characteristics of both electrospraying and conventional solution dry spinning of fibers. The method does not need the use of coagulation chemistry or high temperatures to produce solid threads from solution. This makes the process particularly suited for the production of fibers using large and complex molecules. Because the full potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(93 citation statements)
references
References 127 publications
1
91
0
1
Order By: Relevance
“…Curcumin-loaded PLGA-PEG nanoparticles were 70-300 nm in size and their encapsulation efficiency was 84.5%. It also demonstrated that curcumin has maximum amount of release in a cancer cell-like situation (40°C, pH  5.8) (Kouhi et al 2014, Sadat Tabatabaei Mirakabad et al 2014a, Eatemadi et al 2014, Abbasi et al 2014b, Abbasi et al 2014a, Akbarzadeh et al 2012a.…”
Section: Discussionmentioning
confidence: 92%
“…Curcumin-loaded PLGA-PEG nanoparticles were 70-300 nm in size and their encapsulation efficiency was 84.5%. It also demonstrated that curcumin has maximum amount of release in a cancer cell-like situation (40°C, pH  5.8) (Kouhi et al 2014, Sadat Tabatabaei Mirakabad et al 2014a, Eatemadi et al 2014, Abbasi et al 2014b, Abbasi et al 2014a, Akbarzadeh et al 2012a.…”
Section: Discussionmentioning
confidence: 92%
“…Then, a syringe pump was used to extrude the polymer solution through a spinneret. Finally, the solid fibers can be continuously generated after chemical reaction or solvent evaporating . Unique from these approaches is electrospinning, in which NFs are generated by electrically charging a viscous precursor solution.…”
Section: Microfluidic Spinning Of Nfsmentioning
confidence: 99%
“…Finally, the solid fibers can be continuously generated after chemical reaction or solvent evaporating. [171] Unique from these approaches is electrospinning, in which NFs are generated by electrically charging a viscous precursor solution. In a basic electrospinning setup, a voltage supplier, a metal needle connected to a syringe and a metal collector are three key compositions.…”
Section: Microfluidic Spinning Of Nfsmentioning
confidence: 99%
“…For instance, light sedation coupled with local or regional anesthesia [13,14], may not be appropriate for involved procedures. Drug-loaded nanoparticles provide an excellent solution for higher therapeutic efficacy, reducing drug toxicity and the increasing tropism [15][16][17][18][19][20][21][22][23]. Several nanocarriers are available, including nanoparticles, nanoliposomes, liposomes, micelles, solid lipid particles, quantum dots, surfactant vesicles, and different nanodevices [14,[24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%